Italienische Druckgraphik des 20. Jahrhunderts. (Hannover : Kestner-Museum, 1977)
Adami, Valerio ; Baj, Enrico ; Baratella, Paolo ; Bodini, Floriano ; Bruni, Bruno ; Capogrossi, Giuseppe ; Castellani, Enrico ; Cremonini, Leonardo ; Della Torre, Enrico ; De Vita, Luciano ; Dorazio, Piero ; Fieschi, Gianetto ; Fontana, Lucio ; Francese, Franco ; Gentilini, Franco ; Greco, Emilio ; Guarienti, Carlo ; Guerreschi, Giuseppe ; Guerricchio, Luigi ; Guttuso, Renato ; Maccari, Mino ; Magnelli, Alberto ; Manzu, Giacomo ; Marini, Marino ; Moreni, Mattia ; Music, Zoran Antonio ; Perilli, Achille ; Pomodoro, Arnaldo ; Reggiani, Maruo ; Rui, Romano ; Santomaso, Giuseppe ; Saroni, Sergio ; Sassu, Aligi ; Scanavino, Emilio ; Steffanoni, Attilio ; Tornabuoni, Lorenzo ; Turcato, Giulio ; Vangi, Giuliano ; Zigaina, Giuseppe
Italienische Druckgraphik des 20. Jahrhunderts, Kestner-Museum, Hannover, 26. Mai bis 31. Juli 1977
boek
Keywords: Italië